Vitamin D deficiency in African Americans is associated with a high risk of severe disease and mortality by SARS-CoV-2 - Martín Giménez, Virna Margarita (2020)
COVID-19 is said to be a pandemic that does not distinguish skin color or ethnic origin, but data in many parts of the world, especially in the United States, begins to show that there is a sector of society that is suffering a more significant impact from this pandemic. The black population is being more vulnerable than the white population to infection and death by COVID-19, and hypertension and diabetes mellitus seems to predispose to this vulnerability. Over time, multiple disparities have been observed between the health of blacks and whites, mainly associated with inequalities in the socio-economic scope. However, little by little, some mechanisms and pathophysiological susceptibilities that are directly related to the higher prevalence of multiple diseases in the black population, including infection and death by COVID-19, begin to be elucidated.Plasma vitamin D levels and evolutionary adaptations of the renin-angiotensin-aldosterone system in black people are considerably different between this and other races, and it is well established their role in the development and progression of hypertension and multiple lung diseases, among them, COVID-19 infection.This letter to discuss and proposes whether or not vitamin D and renin-angiotensin-aldosterone system ethnical disparities influence susceptibility to infection and death by COVID-19 in black people and suggests possible mechanisms for this susceptibility.